Visualizing Collagen Network within Human and Rhesus Monkey Vocal Folds Using Polarized Light Microscopy. (February 2013) - Julias, Margaret; Riede, Tobias; Cook, Douglas
Objectives: Collagen fiber content and orientation affect the viscoelastic properties of the vocal folds, determining oscillation characteristics during speech and other vocalization. The investigation and reconstruction of the collagen network in vocal folds remains a challenge, because the collagen network requires at least micron-scale resolution. In this study, we used polarized light microscopy to investigate the distribution and alignment of collagen fibers within the vocal folds. Methods: Data were collected in sections of human and rhesus monkey ( Macaca mulatta ) vocal folds cut at 3 different angles and stained with picrosirius red. Results: Statistically significant differences were found between different section angles, implying that more than one section angle is required to capture the network's complexity. In the human vocal folds, the collagen fiber distribution continuously varied across the lamina propria (medial to lateral). Distinct differences in birefringence distribution were observed between the species. For the human vocal folds, high birefringence was observed near the thyroarytenoid muscle and near the epithelium. However, in the rhesus monkey vocal folds, high birefringence was observed near the epithelium, and lower birefringence was seen near the thyroarytenoid muscle. Conclusions: The differences between the collagen networks in human and rhesus monkey vocal folds provide a morphological basis for differences in viscoelastic properties between species.